A review of traditional and current processing methods used to decrease the toxicity of the rhizome of Pinellia ternata in traditional Chinese medicine. (5th December 2022) - Peng, Wei; Li, Nan; Jiang, Ercheng; Zhang, Chao; Huang, Yongliang; Tan, Ling; Chen, Ruyan; Wu, Chunjie; Huang, Qinwan
Abstract: Ethnopharmacological relevance: The rhizome of Pinellia ternata (Thunb.) Breit, called Pinelliae Rhizoma (PR) and Banxia in Chinese, is a well-known traditional Chinese medicine (TCM) with the functions of " removing dampness-phlegm " and " downbear counterflow and check vomiting ". PR has potential toxic effects that can be detoxified by Fuzhi processing (repeated processing using one or multiple adjuvants) with specific adjuvants. Aim of the study: This paper aims to provide a summary of traditional and current processing methods used to detoxify PR. Materials and methods: The available references of the processing methods of PR from the classic books of Materia Medica, literature, online databases and masters or doctoral theses are collected and summarized. We also discussed the possible processing mechanisms of how we can achieve a safer and effective application of PR via these processing methods. Results: PR cannot be administered orally before processing. PR contains nucleoside alkaloids, cerebrosides, fatty acids, lectin, polysaccharides, and calcium oxalate crystals. To date, although the active substances of PR are still unclear, the toxic components are almost completely clarified as needle-like calcium oxalate crystals (NCOCs) and lectin proteins. Furthermore, the toxic effects of PR include causing death in animals, inflammation, conjunctival irritation, pregnancy toxicity, teratogenicity, visceral toxicity, aphonia and vomiting. From ancient times to now, Fuzhi methods have remained the predominant method for PR processing, and the main adjuvants used are ginger juice, alum, licorice and lime. In addition, detoxification mechanisms are related to removing or damaging the NCOC and lectin in PR based on processing with adjuvants. Currently, Fuzhi processing has been greatly improved, and novel processing technologies with novel adjuvants have been used for PR processing. However, there are still some flaws in PR processing, which should be urgently solved in the future, and clarifying the characteristic bioactive compounds in PR corresponding to its function or effects is the most important step for PR processing. Conclusion: Our present paper reviewed the previous literature regarding all aspects of the processing of PR, and this paper will be helpful for achieving a safer and effective application of PR and its processed products and will also be beneficial for the further optimization of processing technology and clinical medication safety of PR. Graphical abstract: Image 1 Highlights: The toxic components of PR are NCOC and lectin proteins. PR toxicities include inducing inflammtion, conjunctival irritation, pregnancy toxicity, teratogenicity . Fuzhi methods are remain the predominant way for PR processing with ginger, alum, licorice, lime, etc. Clarifying the active compounds in PR is the most important step for the PR processing.